2019
DOI: 10.3892/ijmm.2019.4273
|View full text |Cite
|
Sign up to set email alerts
|

Expression changes of CX3CL1 and CX3CR1 proteins in the hippocampal CA1 field of the gerbil following transient global cerebral ischemia

Abstract: Chemokine C-X3-C motif ligand 1 (CX3CL1) and its sole receptor, CX3CR1, are known to be involved in neuronal damage/death following brain ischemia. In the present study, time-dependent expression changes of CX3CL1 and CX3CR1 proteins were investigated in the hippocampal CA1 field following 5 min of transient global cerebral ischemia (tgCI) in gerbils. To induce tgCI in gerbils, bilateral common carotid arteries were occluded for 5 min using aneurysm clips. Expression changes of CX3CL1 and CX3CR1 proteins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] . As a transmembrane protein specifically expressed in neurons, CX3CL1 can be cut into soluble CX3CL1 and reach the surface of the microglia to bind CX3CR1 and activate microglia when neurons are damaged or exposed to glutamate [19][20] . In this study, we found that PSD-93 could bind NR2B and CX3CL1 to form a complex and promote the release of soluble CX3CL1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] . As a transmembrane protein specifically expressed in neurons, CX3CL1 can be cut into soluble CX3CL1 and reach the surface of the microglia to bind CX3CR1 and activate microglia when neurons are damaged or exposed to glutamate [19][20] . In this study, we found that PSD-93 could bind NR2B and CX3CL1 to form a complex and promote the release of soluble CX3CL1.…”
Section: Discussionmentioning
confidence: 99%
“…CX3 chemokine ligand 1 (CX3CL1) is a chemokine specifically expressed in neurons, while its receptor CX3CR1 is highly expressed in microglia. When neurons are damaged or exposed to glutamate, soluble CX3CL1 disintegrates from its structural domain and binds to CX3CR1 on microglia to activate microglia [19][20] . Therefore, neurons and microglia can communicate through CX3CL1/CX3CR1 signals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSD-93 can interact with other proteins with its function structure domain and change the structure and function of other proteins [25][26] . As a transmembrane protein speci cally expressed in neurons, CX3CL1 can be cut into soluble CX3CL1 and reach the surface of the microglia to bind CX3CR1 and activate microglia when neurons are damaged or exposed to glutamate [19][20] . In this study, we found that PSD-93 could bind NR2B and CX3CL1 to form a complex and promote the release of soluble CX3CL1.…”
Section: Discussionmentioning
confidence: 99%
“…CX3 chemokine ligand 1 (CX3CL1) is a chemokine speci cally expressed in neurons, while its receptor CX3CR1 is highly expressed in microglia. When neurons are damaged or exposed to glutamate, soluble CX3CL1 disintegrates from its structural domain and binds to CX3CR1 on microglia to activate microglia [19][20] . Therefore, neurons and microglia can communicate through CX3CL1/CX3CR1 signals.…”
Section: Introductionmentioning
confidence: 99%
“…Its only receptor CX3CR1 is highly expressed in microglia and its main forms are membrane binding and soluble. When neurons are damaged or exposed to glutamate, soluble CX3CL1 disintegrates from its structural domain and binds to CX3CR1 on microglia to activate microglia [18][19] , directly inducing multiple functions of microglia. Therefore, neurons and microglia can communicate through CX3CL1/CX3CR1 signals.…”
Section: Introductionmentioning
confidence: 99%